Treatment and counselling preferences of postpartum women with and without symptoms of (childbirth-related) PTSD: findings of the cross-sectional study INVITE - Rosa Hannele Horstmann; Lara Seefeld; Julia Schellong; Susan Garthus-Niegel (BMC Pregnancy and Childbirth)
Abstract Background Post-traumatic stress disorder (PTSD) in the postpartum period is a prevalent yet under-researched mental health condition. To date, many women who suffer from postpartum PTSD remain unrecognized and untreated. To enhance the accessibility of help for these women, it is crucial to offer tailored treatment and counselling services that align with their needs. This study aimed to understand how support preferences differ between women with and without postpartum PTSD, considering the two subgroups of postpartum PTSD: childbirth-related PTSD (CB-PTSD) and general PTSD (gPTSD). Methods This study used data from the cross-sectional INVITE study, comprising telephone interviews with N = 3,874 women conducted six weeks to six months after childbirth. The City Birth Trauma Scale (City BiTS) was used to assess CB-PTSD, while the Primary Care Posttraumatic Stress Disorder Screen for DSM-5 (PC-PTSD-5) was used to assess gPTSD. Service preferences and preferred modes of service provision were measured with self-developed questionnaires. Analyses of variance were used to identify differences between groups. Results The support services (family-)midwives and family, friends, or colleagues and the service provision mode as in person communication were preferred most by women across groups. The analyses revealed that women with CB-PTSD had lower overall preferences for services compared to women without postpartum PTSD. Women with CB-PTSD also showed less preference for psychotherapeutic services (e.g. outpatient treatment, inpatient clinics) compared to women without postpartum PTSD. Regarding modes of service provision, women with gPTSD had a higher preference for all service modes compared to women with CB-PTSD and those without postpartum PTSD, with a stronger preference for both direct (e.g. in person, video conference) and delayed communication (e.g. chat, e-mail). Conclusion This study was the first to explore the support preferences of women experiencing symptoms of postpartum PTSD. Findings suggest that women differ in their preferences, contingent upon the subgroup of postpartum PTSD. According to women's overall preferences, the expansion and further training of (family-)midwife services is recommended. By tailoring support services accordingly to women’s preferences, it may be possible to bridge the treatment gap for postpartum PTSD and to improve the well-being of affected women and their families.